Genomic Profiling of Driver Gene Mutations in Chinese Patients With Non-Small Cell Lung Cancer - Meng, Hongxue; Guo, Xuejie; Sun, Dawei; Liang, Yuebin; Lang, Jidong; Han, Yingmin; Lu, Qingqing; Zhang, Yanxiang; An, Yanxin; Tian, Geng; Yuan, Dawei; Xu, Shidong; et al. (Frontiers in Genetics, 2019)
Worldwide, especially in China, lung cancer accounts to a major cause of mortality related to cancer. Treatment decisions mainly depend on oncogenic driver mutations, which offer novel therapeutic targets for anticancer therapy. However, studies of genomic profiling of driver gene mutations in mainland China are rare. Hence, this is an extensive study of these mutations in NSCLC Chinese patients. Comparison of driver gene mutations of lung adenocarcinoma with other races showed that the mutational frequencies were similar within the different East Asian populations, while there was quite difference between East Asian and non-Asian populations. Furthermore, four promising candidates for druggable mutations of EGFR were revealed, that open up avenues to develop and design personal therapeutic approaches for patients harboring mutations. These results will help to develop personalized therapy targeting NSCLC.